Input-series-output-parallel Dual Full-bridge DC/DC Converter Based on Interleaving Control Method - 吴恒亮; 谢伟 (Kongzhi Yu Xinxi Jishu)
An input-series-output-parallel (ISOP) circuit topology is used for the DC/DC conversion with high input voltage and high output current. The key issue of ISOP is the dynamic voltage sharing of input capacitors. It points out the reason of the input voltage unsharing and output current unsharing for dual full-bridge converter of ISOP. At the same time, on the basis of theoretical analysis, it modeled and simulated an interleaving control by Simulink. The results verified the effectiveness of the proposed method.